Social reconstruction scale: Measuring intergroup relations after conflict - Čorkalo Biruški, Dinka (Array, 2009)
The major and most challenging task for groups after conflict is to repair damaged social ties and/or establish new social relations. Post-conflict intergroup relations are loaded with memories of mutual wrongdoings, suffering and betrayals that have been done during the conflict. These emotional burdens are major obstacles for establishing mutual trust, cooperation between groups and positive emotional relations. In order to describe the improvement or lack of progress in the intergroup relations after the conflict, we refer to the concept of social reconstruction rather than reconciliation, which we regard as being more appropriate for interpersonal level of analysis. We define social reconstruction as a process within and around a community which brings its damaged social functioning to an improved level of interpersonal and groups relations and renews the social fabric of the affected community (Ajdukovic, 2004 ; 2005). Following our own understanding of this process and relying on Nadler’ s (2002) conception of intergroup reconciliation, we operationalized social reconstruction as a multifacet construct containing components of intergroup cooperation, intergroup empathy, intergroup trust, a need for apology from the outgroup, and intergroup forgiveness. We developed the instruments with a set of 21 items that was administered to the representative sample of adult Croats (N=210) and Serbs (N=123) aged 18 to 65 years living in the city of Vukovar. The factor structure of the Social Reconstruction Scale was compared for the two ethnic groups showing that underlying dimensions for some scale components are not always the same. Results for various aspects of social reconstruction differed in these two ethnic groups, depending on the degree of their victimization and reflecting differences in how they perceived their recent conflict and understand the possibilities for social recovery.